Shifting Cultivation Dynamism in Orissa, India - Sharma, R. A. (Indian Forester, 1994)
Shifting cultivation evolved in the socio-economic environment of ancient India, characterised by surplus land, and scarcity of labour and capital resources. The age-old practice has become unviable, leading to the degradation of forests and tribal economy, due mainly to the changes in socio-economic and agro-ecological parameters which sustained it. Land-based technologies such as labour-intensive agroforestry systems, providing basic needs and employment, may be implemented by using surplus labour and wastelands in order to control shifting cultivation.